THE USE OF SMARTPHONE IN DEVELOPING STUDENTS’ READING COMPREHENSION FROM PERSPECTIVE OF GENDER DIFFERENCES - Mohamad Ibrahim Baliu; Karmila Machmud (English Language Teaching and Research, 2017)
This study aims to know if there is a difference of students’ reading comprehension between students taught with and without Smartphone, to investigate deeply if there also an interaction between using Smartphone toward students’ reading comprehension, to find out the difference of students’ reading comprehension between male students who use Smartphone and do not use Smartphone, to dig up any difference of students’ reading comprehension between female students who use Smartphone and do not use Smartphone. This study is an experimental study which conducted on the seventh-grade students of SMP Negeri 1 Batudaa focused on two classes. One class as the treatment class consists of 20 students and one class as the control class consists of 20 students. They were selected by purposive sampling. The method used in this research was experimental method, and the data was collected by using test. The design used in this research is factorial design 2 x2 by using ANAVA.The result of this study has shown: (1) The students’ reading comprehension that have been taught by using Smartphone is better than students’ reading comprehension which taught without using Smartphone; (2) there is an interaction between using Smartphone toward students’ reading comprehension; (3) there is a difference of students’ reading comprehension between male students who use Smartphone and do not use Smartphone; (4) there is a difference of students’ reading comprehension between female students who use Smartphone and do not use Smartphone. The applying the suitable model of teaching gave the significant influence towards students’ reading comprehension. Key words: Smartphone, Reading Comprehension, and Gender Differences